2017
DOI: 10.1111/eci.12756
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of the restriction method in two large observational studies of body mass index and mortality among adults

Abstract: Background A method applied in some large studies of weight and mortality is to begin with a well-defined analytic cohort and use successive restrictions in order to control for methodologic bias and arrive at final analytic results. Materials and methods Two observational studies of body mass index and mortality allow a comparative assessment of these restrictions in very large data sets. One was a meta-analysis of individual participant data with a sample size of 8 million. The second was a study of a Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
(84 reference statements)
2
8
0
Order By: Relevance
“…Yi et al . in particular still found hazard ratios below 1 for overweight subjects, suggesting that in fact, the GBMC findings are misleading and the applied restrictions introduced bias to the GBMC data . The Yi paper is instead consistent with the findings of Flegal et al .…”
Section: The Discussion In the Context Of Other Published Studiessupporting
confidence: 76%
See 1 more Smart Citation
“…Yi et al . in particular still found hazard ratios below 1 for overweight subjects, suggesting that in fact, the GBMC findings are misleading and the applied restrictions introduced bias to the GBMC data . The Yi paper is instead consistent with the findings of Flegal et al .…”
Section: The Discussion In the Context Of Other Published Studiessupporting
confidence: 76%
“…Yi et al in particular still found hazard ratios below 1 for overweight subjects, suggesting that in fact, the GBMC findings are misleading and the applied restrictions introduced bias to the GBMC data. 29 The Yi paper is instead consistent with the findings of Flegal et al 30 In particular, the data from Yi et al showed that overweight was not associated with an increased risk of death (hazard ratio of 0.85) and grade 1 obesity (BMI 30-35) was associated with only a very small increased risk of death (hazard ratio of 1.06).…”
Section: Unaddressed Biassupporting
confidence: 64%
“…cancer-specific survival or overall survival) is less consistent, and for many malignancies, overweight or obesity is associated with a survival advantage ( Figure 1). [17][18][19][20][21][22] Other explanations involve BMI being too crude a measure to be useful at the individual patient level. For example, in a pooled analysis of 22 randomized therapeutic treatment trials that included 11 724 patients with cancer, 67% were overweight/obese (BMI ≥25 kg/m 2 ) at the time of enrolment (e.g.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…However, when these methodological concerns are empirically tested, many are not substantiated and the previously observed associations persist. [17][18][19][20][21][22] Other explanations involve BMI being too crude a measure to be useful at the individual patient level. 23 BMI does not differentiate lean mass from adipose mass, nor does it describe regional adipose tissue deposition (e.g.…”
Section: The Epidemiology Of Body Composition In Cancermentioning
confidence: 99%
“…A further threat to the validity of our estimates is potential unobserved confounding by undiagnosed ovarian cancer (often referred to as “reverse causation” [ 34 ]) if these conditions are symptomatic enough to induce a change in body weight. We, therefore, assumed 3 years of minimum latent period required for weight change due to unobserved disease to affect the outcome and excluded events that occurred during this time [ 35 ]. The statistical analysis was performed using Stata 15.1.…”
Section: Methodsmentioning
confidence: 99%